THE DEVELOPMENT OF A WEB-BASED ENGLISH WETLANDS DICTIONARY TO SUPPORT THE DISSEMINATION OF ENGLISH FOR WETLANDS IN SOUTH KALIMANTAN - Elsa Rosalina; Nasrullah Nasrullah; Eka Puteri Elyani; Inayati Fitriyah Asrimawati; Soraya Istiqamah; Meyklen Sulawati (Universitas Lambung Mangkurat, 2026)
Abstract: The integration of technology has become a vital component of modern education systems, especially in creating flexible learning environments. In the English for Specific Purposes (ESP) field, learning materials that include contextualized vocabulary are important tools to facilitate students' comprehension of specialized terminology related to a particular field of study. Wetlands are a significant component of the cultural identity of the region of South Kalimantan. However, students often face difficulties in understanding wetland-related terminology because such materials are not available in English language dictionaries. Thus, this research aims to develop a web-based English-Indonesian wetlands dictionary to facilitate the delivery of English for Wetlands learning materials.This research followed the Research and Development (R&D) model as described by Sugiyono. This model has seven steps to complete the research. The steps include needs analysis, product design, development, validation, testing, revision, and final product. The product was validated through a test involving 35 students from three higher learning institutions in the region of South Kalimantan. The research used a Likert-type questionnaire with 23 items to collect the data.From the findings, it is evident that the developed dictionary generated positive feedback from the users. It was considered to be very accessible and useful for the learners to understand the terms concerning the wetlands. Almost all the respondents were of the opinion that the developed dictionary could enhance the improvement of English vocabulary acquisition.In conclusion, the web-based wetlands dictionary is an effective tool for ESP learning and English learning with the inclusion of information concerning the wetlands of South Kalimantan. Keywords: English for Specific Purposes, English for Wetlands, Web-Based Dictionary